Performance of C,N-Impregnated Photocatalyst Coupled with Continuous-Flow Reactor for Removal of Gaseous Aromatic Pollutants - Jo, Wan-Kuen; Kang, Hyun-Jung (Asian Journal of Chemistry, 2013)
Previous activity tests of carbon and nitrogen co-impregnated photocatalysts (C and N-impregnated-TiO2) for environmental pollution controls were primarily performed in the aqueous phase to investigate the decomposition of water pollutants. This study examined the photocatalytic activities of C,N-TiO2 photocatalysts for the purification of indoor-level gaseous organic compounds under different experimental conditions. The as-prepared C,N-TiO2 and unmodified TiO2 powders were characterized using XRD, SEM, diffuse reflectance UV-VIS-NIR spectra and Fourier transform infrared spectra. The C,N-TiO2 powders exhibited a shift in the absorbance spectrum towards the visible light region when compared to TiO2 powders, indicating that the as-prepared C,N-TiO2 photocatalyst could be effectively activated by visible-light irradiation. The surface characteristics of the two types of photocatalysts differed. Additionally, the average photocatalytic degradation efficiencies for benzene, toluene, ethyl benzene and xylene (BTEX) obtained from the C,N-TiO2 system were 27, 81, 95 and 99 %, respectively, whereas those of the TiO2 powders were close to zero, 19, 47 and 56 %, respectively. Under the experimental conditions used in this study, the photocatalytic degradation efficiencies for BTEX were higher for the photocatalytic system with the fluorescent lamp than for that with light-emitting diodes.